The Evolution of Money To Cryptocurrency: Are They Eligible To Be Islamic Digital Money - Yunita, Patria (UI Scholars Hub, 2022)
The cryptocurrency was a very popular issue in recent years. There was a debate among scientists regarding the prohibition of cryptocurrencies as a medium of exchange. Some Islamic institutions use cryptocurrencies and blockchain platforms in the financial transaction. This study analyzes the arguments of classical and modern Muslim scientists regarding the evolution of money to become modern Islamic digital money in the form of cryptocurrency. We used ARCH GARCH to predict the volatility of cryptocurrencies. Our samples are Bitcoin, Ethereum, IDR Token, and Tether USD Token. IDRT and USDT are stablecoins. Bitcoin and Ethereum are cryptocoin. We use daily data of cryptocurrency fluctuations from August 7, 2015, to May 21, 2021. The data were taken from the official website for cryptocurrency transactions, coinmarketcap.com and blockchain. com. This study proves that Bitcoin and Ethereum are types of cryptocurrencies which have very high volatility. Meanwhile, IDRT Rupiah Token and Tether USD Token are more stable types of cryptocurrencies. In terms of using digital money for modern Islamic financial transactions, we suggest using cryptocurrencies of the token type.